In vitro organogenesis in Albizia guachapele, Cedrella odorata and Swietenia macrophylla (Fabaceae, Meliaceae) - Lisette Valverde Cerdas (Revista de Biología Tropical, 1998)
Regeneration of adventitious buds was achieved from hypocotyl explants of Albizia guachapele (Guayaquil) and Cedrella odorata (Spanish cedar), and from epicotyl explants from Swietenia macrophylla (Honduran Mahogany). Seeds were obtained from CATIE's Latin American Forest Seed Bank and germinated under aseptic conditions. Four explants were cultured in each Petri dish on half strength modified Murashige and Skoog basal medium, and five concentrations of BA (benzyladenine) were studied; A. guachapele and S. macrophylla responded positively to the presence of BA in the culture medium. Otherwise, Cedrella odorata required media supplemented with citokinin and auxin combinations to induce adventitious buds.